Classical Music Futures - Smith, Neil Thomas; Peters, Peter; Molina, Karoly (2024)
This volume brings together contributions from a wide range of international academics and practitioners. It traces innovations within classical music practice, showing how these offer divergent visions for its future. The interdisciplinary contributions to the volume highlight the way contrasting ideas of the future can effect change in the present. A rich balance of theoretical and practical discussion brings authority to this collection, which lays the foundations for timely responses to challenges ranging from the concept of the musical work, and the colonial values within Western musical culture, to unsustainable models of orchestral touring. The authors highlight how labour to meet the demands of particular futures for classical music might impact its creation and consumption, presenting case studies to capture the mediating roles of technology and community engagement. This book will be of interest to scholars and students in the fields of musicology and the sociology of music, as well as a general audience of practitioners, freelance musicians, music administrators and educators.